2023
DOI: 10.11591/ijece.v13i1.pp435-442
|View full text |Cite
|
Sign up to set email alerts
|

A genetic algorithm for shortest path with real constraints in computer networks

Abstract: <span lang="EN-US">The shortest path problem has many different versions. In this manuscript, we proposed a muti-constrained optimization method to find the shortest path in a computer network. In general, a genetic algorithm is one of the common heuristic algorithms. In this paper, we employed the genetic algorithm to find the solution of the shortest path multi-constrained problem. The proposed algorithm finds the best route for network packets with minimum total cost, delay, and hop count constrained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, prior research has demonstrated that using a tutorial video in the vocational education process has improved student learning outcomes. Prior research has produced videos limited to tutorial videos with no animation, textual, or voice explanation (Alghamdi et al, 2023;Hafis et al, 2023;Richardo et al, 2023). Therefore, this study benefits from earlier studies in that the application video includes animation, audio, and explanatory text in addition to tutorials on modifying the computer bios, making it easier for students to comprehend the course material (Lestari et al, 2023;Sansi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, prior research has demonstrated that using a tutorial video in the vocational education process has improved student learning outcomes. Prior research has produced videos limited to tutorial videos with no animation, textual, or voice explanation (Alghamdi et al, 2023;Hafis et al, 2023;Richardo et al, 2023). Therefore, this study benefits from earlier studies in that the application video includes animation, audio, and explanatory text in addition to tutorials on modifying the computer bios, making it easier for students to comprehend the course material (Lestari et al, 2023;Sansi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Network computer engineering is one of the majors in vocational schools, which aims to equip students with today's digital technology. In this department, students are equipped with computer programming skills, computer networks and the internet, and skills to create websites on the internet (Alghamdi et al, 2023;Shan, 2023). Through innovative learning by using learning videos, students will more easily understand basic computer and network material.…”
Section: Introductionmentioning
confidence: 99%
“…In power systems, the artificial bee colony (ABC) algorithm has been harnessed to enhance the location optimization of capacitor banks and distributed generators, focusing on improving reliability and diminishing power loss [3]. Meanwhile, the GA has demonstrated its prowess in optimizing packet routes within computer networks, aiming to minimize delay, hop count, and overall cost [4].…”
Section: Introductionmentioning
confidence: 99%